Efektivitas Penggunaan Metode Role Play untuk Meningkatkan Keterampilan Berbicara Bahasa Arab - Albana, Restu Kurniawan; Arifin, Syamsul; Ridlo, Ubaid; Wahab, Muhbib Abdul; Susiawati, Wati (Kopertais Wilayah I DKI Jakarta dan Banten, 2023)
This study aims to examine the effectiveness of the Role Play method in improving Arabic speaking skills. This research is significant because several issues in teaching speaking skills have been identified, including students’ lack of confidence when speaking Arabic due to their fear of making mistakes, which is caused by their limited vocabulary. Additionally, Arabic language instruction often focuses solely on vocabulary teaching, and teachers have not yet implemented engaging methods and strategies in Arabic language teaching. This study employs a quantitative approach with a quasi-experimental design involving two groups of students: an experimental group using the Role Play method and a control group not using the Role Play method. The research data was collected through oral tests (pre-test and post-test) and analyzed using t-tests and N-Gain tests to determine the effectiveness and degree of effectiveness of the method. After applying the treatment, the average score of the experimental group increased to 75.37, compared to 41.47 before the treatment. Meanwhile, the control group’s average pre-test score was 38.95, and their post-test score was 41.89. The t-test results showed a value of 19.96, with a t-table value of 1.68 at a 5% significance level and 2.43 at a 1% significance level. This indicates that the t-test value is greater than the t-table value, meaning the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted, signifying that the Role Play teaching method effectively improves Arabic speaking skills. Furthermore, the N-Gain test was conducted to determine the level of effectiveness, which yielded a result of 0.6. This value falls within the range of >0.03 and <0.07, indicating that the effectiveness of this teaching method is categorized as moderate.